Effect of air pollution on FVC, FEV1 and FEV1/FVC% of the traffic policemen in Dhaka ci - Ahmed, Shahriar; Akter, Qazi Shamima; Eva, Hossneara; Bhowmik, Mita (Journal of Bangladesh Society of Physiologist, 2016)
Background: Due to large number of vehicles, air pollution is increasing day by day in Dhaka city. Automobile exhaust cause acute and chronic respiratory disease in traffic policemen as they are exposed to air pollution for prolong period of time. Objective: To observe the effect of long term exposure to air pollution on FVC, FEV1 and FEV1/FVC% of traffic policemen. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College (DMC), Dhaka from July 2014 to June 2015. Fifty apparently healthy traffic policemen with the age 25 to 45 years were selected as study group. Fifty age and BMI matched healthy male subjects were selected as control. The study subjects were selected from different traffic junctions and the control from different offices of Dhaka city. FVC, FEV1 and FEV1/FVC% of all the subjects were measured by a digital spirometer. Statistical analysis was done by Independent sample t test. Results: In this study FVC, FEV1 and FEV1/FVC were significantly (p< 0.001) lower in the traffic policemen than the control group. Conclusion: From the result of this study it can be concluded that prolonged exposure to air pollution may decrease pulmonary function of the traffic policemen in Dhaka city. Bangladesh Soc Physiol. 2016, December; 11(2): 39-42